Intradermal infections by chigger mites (Hannemania spp.) in the Andean frog Telmatobius atacamensis (Anura, Telmatobiidae) - Quinzio, Silvia Inés (2015)
Here, we report the infection of adults of the Andean frog Telmatobius atacamensis (Anura, Telmatobiidae) by leeuwenhoekiid mites of the genus Hannemania and describe the histological characteristics of the normal and infected skin and the mite's larval capsule.